Innovation in Guidance and Counseling Management Based on Digital Technology in Schools - Nora Rustianti; Rafiatul Mahmudah; Fridameka Koswara; Dasril Dasril; Syaiful Nasyar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The development of digital technology offers significant opportunities to improve the effectiveness of guidance and counseling (BK) management in schools. In today's digital era, BK services are required to adapt to technological changes to meet students' needs more quickly, precisely, and efficiently. This article aims to examine various innovations in digital technology-based Guidance and Counseling management through a literature review of books, scientific journals, and other relevant sources. The study's findings indicate that the use of information technology, such as counseling data management applications, BK information systems, digital communication platforms, and interactive media, can improve data management efficiency, from recording and storing to analyzing counseling data in a systematic and integrated manner. The use of this technology also strengthens the quality of interactions between counselors and students, both through face-to-face and online services. The implementation of digital-based BK management innovations also supports more accurate reporting processes and data-driven decision-making. However, its implementation still faces various challenges, such as limited digital competence of counselors and ethical and data confidentiality issues. Therefore, a development strategy and supporting policies are needed so that digital technology-based BK management innovations can be implemented optimally and sustainably.